AI-GENERATED VISUAL ART AND ITS ETHICAL IMPLICATIONS IN ACADEMIA - Hoque, Mohammed Shamsul; R.Vasanthan,; Dzuvichu, Khriereizhunuo; Saini, Jyoti; Parashar, Komal; Grover, Madhur (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The swift growth of the artificial intelligence (AI) has transformed the world of art, especially in the shape of AI-generated visual art. In academic life this phenomenon presents very profound concerns about authorship, creativity and social responsibility. In this paper, the author discusses the intersection of AI-generated art and education, and addresses the potential and the possible social implications of the intersection. It starts with significant technical foundations of the art of AI like neural networks and generative adversarial networks (GANs), and signals how this dichotomy of human authorship and machine authorship has changed. On academic grounds, this argument concerns the question of whether AI, in fact, can be called an artist, or merely a tool that can facilitate human creativity. This study is focused on ethical question. Authorship and intellectual property questions are also disruptive to the conventional academic practices, because AI systems frequently produce works, which lack a clear human provenance. Also, creativity and imitation appear to be significant issues in the area of education, in which students are able to produce art with minimal human involvement via AI tools. The necessity of transparency (the explanation of how AI helped in schoolwork and research) reveals the fact that academic ethics should be preserved even more. The discussion continues to address more about the higher contribution to imagination and learning. With the introduction of AI art into school education, the dilemma of how to add it without entering the trap of students who over-depend on technologies and become responsible innovators will continue to gain topicality. This research provides a mechanism through which AI art can be socialized and made productive by universities through the examination of both controversies and successful collaborations. In summary, it supports a moderate position that is receptive to creative innocence, but also concedes with technological innovation as a teaching incentive.